Building Religious Character through Suluk on Multiethnic Students of Thariqah Al-Mu'min Community in West Kalimantan - Muhammad Edi Kurnanto; Sumin Sumin; Darmiyati Zuchdi; Sumar’in Asmawi (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
The moral damage caused by the erosion of positive values and national character is quite concerning. This phenomenon has encouraged government concern through strengthening students’ character. Strengthening students' character through formal education has not produced significant results, as evidenced by the many symptoms of moral decay and crime involving students in Indonesia. To overcome this, an alternative strategy is needed to elaborate between character education based on thoughts and hearts, which non-formal educational institutions can carry out. This research explores the suluk method as an alternative for forming religious characters for students who practice the Thariqah Al-Mu'min in West Kalimantan. This study uses a case study method and a qualitative approach. The research results found that; suluk can shape the religious character of students who practice the Al-Mu'min Order; these characteristics are; peace of mind, discipline, enthusiasm in worship, gratitude, trustworthiness, honesty, understanding the purpose of life, feeling close to Allah, feeling more moral than before, feeling more important in controlling lust, respecting others, increasing love for the hereafter, increasing longing for Allah and His Messenger, and sincere in worship. Suluk can give a deep religious impression and feel the presence of God in his life. This study emphasizes the importance of using the method of suluk in non-formal Islamic societies and formal Islamic education institutions such as Islamic boarding schools and religious colleges to form pious students. However, suluk also has weaknesses; only a thariqah practitioner can practice suluk. The students must also be physically and mentally prepared because the suluk method requires seriousness to form a religious character in the performer.